The paths of inclusion of people with disabilities: the evolution through the professional and technological education of the Federal Network (Research, Society and Development, 2021)
This article aims to present the historical path of inclusion of people with disabilities in education, emphasizing professional and technological education in the federal network. Thus, under a critical vision, a hard path was observed, full of struggles and achievements in the inclusion of people with disabilities in professional and technological training. Historical aspects go through the initial process of acceptance of people with disabilities in society until their insertion in education. The origin of this process was marked by limited training due to disability, however, the evolution of the educational process in the face of people with disabilities is noticeable. With new inclusion policies, such as the creation of service Centers for People with Specific Educational Needs (NAPNES), the federal network training enabled access to assistive Technologies that promote the entry, permanence and successful completion of their training taking into account considering its insertion in society and in the world of work.